Análise da arborização urbana em loteamentos da Zona Norte de Maringá, Paraná - 2000 a 2010 - Bonjorno, Lessyane Rezende de Matos Souza (2012)
In the urban planning process, arboreal setting has a special role when it comes to life quality and city aesthetics. Thus in the urban area it is acceptable to have predominantly natural vegetation and non-inhabited sites. Nonetheless, there might have a few drawbacks when arboreal setting is not well done or done recklessly. That is due to private initiatives that lack technical knowledge, once they sow in irregular places baring no compatibility with planned proposals. Such situation reflects the inefficiency of green areas in the urban scenario, which is meant to convey physical and schycological comfort. Given that, this research had as its leading purpose to evaluate the north part of Maringá in its arboreal setting which is going through a road follow-up in residential lots. This was because the referred area is currently undergoing an intense urban expansion. In that sense, this work made use of a qualitative arboreal inventory, coming up with a data in the analysis of arboreal projects intending to: firstly characterize and secondly gauge the arboreal species in loco in five apportionments implemented from 2000 to 2004. The result unveiled that the arboreal planning in the aforementioned areas obeys the city's Arboreal Director Plan, though its implementation is interfered with the lack of precautions, which consequently smudges the road landscape perspective of the allotments; in other words, species inapt to grow on the streets are spread in those areas.